PERLINDUNGAN HUKUM TERHADAP KORBAN SALAH TANGKAP ATAU ERROR IN PERSONA (STUDI KASUS PUTUSAN PENGADILAN NEGERI SEKAYU NOMOR 330.PID.SUS/2020/PN.SKY) - Yunita Dimer Bustomi; R Rahaditya (Fakultas Hukum Universitas Tarumanagara, 2021)
False arrest is a mistake about the person in question or a mistake about the person and is a problem in the Criminal Justice System because of a violation of rights at one or all levels of examination. These violations can be in the form of procedural violations, administrative violations, violations against the suspect's personal self to serious violations such as fabricating witnesses and engineering evidence of a case. Criminal law aims to protect and save individuals from crimes in society, so that this goal must be maintained so that it is not possible for a crime to escape due to an error in the investigation or maybe vice versa there is no crime which due to an incorrect method of investigation causes innocent people to suffer and be punished. crime without being based on the law. Legal protection for victims of wrongful arrest in criminal justice is regulated in Law no. 8 of 1981 concerning the Criminal Procedure Code (KUHAP), namely in the form of Compensation and Rehabilitation. Provisions regarding compensation include acts of arrest, detention, prosecution, or trial or because they are subject to other actions without reasons based on law, or because of errors regarding the person or the law that is applied. The application for compensation for the decisions that have been submitted until the court stage is completed by the District Court. Meanwhile, rehabilitation can be obtained by someone who has been released or released from all legal claims whose decision has permanent legal force. The amount of compensation claims that can be submitted by victims of wrongful arrests based on PP No. 92 of 2015 concerning the Second Amendment to Government Regulation No. 27 of 1983, namely the amount of value obtained by a person who is acquitted or dismissed from all legal claims whose decision has permanent legal force. Meanwhile, rehabilitation is given and submitted at the same time in a court decision that has permanent legal force.